Quantification of apocarotenoids in commercial Indian (Kashmiri) saffron using UV-Vis spectroscopy and HPLC analysis - Tahir ul Gani MIR; Jaskaran SINGH; Saurabh SHUKLA (Acta Agriculturae Slovenica)
Saffron is considered as the most expensive spice in the world. Due to low production, high demand and high cost, saffron is very prone to adulteration for economic benefits while putting public health at risk. The most significant characteristic for determining the quality of the saffron is coloring strength (crocin content), which is determined by measuring UV-Vis absorption at 440 nm in the aqueous preparations of this spice. Picrocrocin and safranal are other key components used to determine saffron quality. This article aims to examine the quality of commercial saffron obtained from various geographical locations of Kashmir (India) by determining their apocarotenoid content using UV-Vis spectrophotometry followed by high-performance liquid chromatography (HPLC) to determine the concentration of saffron metabolites (crocin, picrocrocin and safranal). A total of 31 samples from different origins were used in this study. The UV-Vis spectrophotometric results showed that among 31, only 14 samples fell into grade I, while 9 samples fell in grade II and 5 samples fell in grade III of the ISO category. The remaining 3 samples could not satisfy ISO standards, which indicates that these samples were adulterated. The determination of apocarotenoid content using HPLC analysis varied significantly among samples. These variations may be due to different drying and storage conditions or adulteration.